2023
DOI: 10.1177/23259671231179757
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphological Characteristics as Risk Factors for Anterior Cruciate Ligament Injury: Comparison Between Contact and Noncontact Injury

Abstract: Background: Altered bone morphologies are considered risk factors for noncontact anterior cruciate ligament (ACL) injuries. Purpose/Hypothesis: This study aimed to investigate bone morphological characteristics as risk factors for ACL tears in contact injuries and compare these factors with those for noncontact ACL injuries. We hypothesized that altered bone morphologies would also be risk factors for contact ACL injury. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Enrolled were patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Similar to PTS, intercondylar notch parameters have been extensively studied as a risk factor in the context of ACL injuries. In the ACL, more narrow intercondylar notches may contribute to the impingement of the ligament [45,46]. Additionally, it is postulated that smaller notches result in a smaller cruciate ligament, decreasing the amount of loading force that can be withstood [16].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to PTS, intercondylar notch parameters have been extensively studied as a risk factor in the context of ACL injuries. In the ACL, more narrow intercondylar notches may contribute to the impingement of the ligament [45,46]. Additionally, it is postulated that smaller notches result in a smaller cruciate ligament, decreasing the amount of loading force that can be withstood [16].…”
Section: Discussionmentioning
confidence: 99%
“…A large knee valgus angle during cutting has been identified as a risk factor for ACL injuries [ 54 ]. An important takeaway from this study is that KT significantly reduces the knee valgus angle compared to NT in ACLR athletes during 90° cutting.…”
Section: Discussionmentioning
confidence: 99%
“…In human ACL injury, the most common mechanism of injury is sudden pivoting or cutting maneuver which often occur during sports such as soccer, basketball, and football. Non-contact injury is also reported, with risk factors associated with tearing of the ACL including sex (female > male), and numerous bone morphologic characteristics such as lateral femoral condylar ratio, notch width index, and lateral posterior tibial slope ( 17 ). In dogs, one study found an association between tibial anatomical-mechanical axis angle and CCL injury ( 18 ).…”
Section: Discussionmentioning
confidence: 99%